A branch-and-bound procedure for forest harvest scheduling problems addressing aspects of habitat availability - Neto, Teresa; Constantino, Miguel; Martins, Isabel; Pedroso, João Pedro (International transactions in operational research, 2013)
In the literature, the most widely referred approaches regarding forest harvesting scheduling problems involving environmental concerns have typically addressed constraints on the maximum clear‐cut area. Nevertheless, the solutions arising from those approaches in general display a loss of habitat availability. Such loss endangers the survival of many wild species. This study presents a branch‐and‐bound procedure designed to find good feasible solutions, in a reasonable time, to forest harvest scheduling problems with constraints on the clear‐cut area and habitat availability. Two measures are applied for the habitat availability constraints: the area of all habitats and the connectivity between them. In each branch of the branch‐and‐bound tree, a partial solution leads to two children nodes, corresponding to the cases of harvesting or not harvesting a given stand in a given period. Pruning is based on constraint violations or unreachable objective values. Computational results are reported.